A Randomized, blinded assessor study to Evaluate the efFIcacy and safety of etanercept 50 mg once weekly plus as Needed topical agent vs. Etanercept 50 mg twice weekly in patients with moderate to severe plaque psoriasis (REFINE). (1st July 2014) - Papp, K.A.; Barber, K.; Bissonnette, R.; Bourcier, M.; Lynde, C.W.; Poulin, Y.; Shelton, J.; Toole, J.; Vieira, A.; Poulin‐Costello, M.
Abstract: Background: Topical corticosteroids are used with systemic therapies for treatment of plaque psoriasis, but data from randomized clinical trials to document efficacy of combination therapy are lacking. Objective: To evaluate efficacy and safety of adding topical corticosteroid therapy from the time that etanercept dosage is reduced from initial label dose [50 mg twice weekly (BIW)] to maintenance dose [50 mg once weekly (QW)]. Methods: In this phase 3b, multicentre, randomized, open‐label study, patients with moderate‐to‐severe plaque psoriasis received etanercept 50 mg BIW for 12 weeks, and then were randomized to etanercept 50 mg BIW or 50 mg QW plus topical agent as needed to achieve static physician global assessment (sPGA) status of clear for 12 weeks. Endpoints included percentage change in Psoriasis Area and Severity Index (PASI) score from week 12 to week 24 (primary endpoint); proportion of patients achieving 50% improvement in (PASI 50), PASI 75 and PASI 90; patients achieving sPGA of clear/almost clear; and change in affected body surface area (BSA). Results: Mean difference [95% confidence interval (CI)] between etanercept arm ( n = 140) and etanercept plus topical arm ( n = 142) in change in PASI score from week 12 to week 24 was 16.2% (−3.5%, 35.8%). PASI response rates were similar between groups. Percentage (95% CI) of patients achieving sPGA status of clear/almost clear was 40.6% (32.5%, 48.6%) and 45.8% (37.6%, 54.0%) at week 12 for patients in etanercept and etanercept plus topical arms, respectively, and 53.5% (45.3%, 61.7%) and 45.4% (37.2%, 53.6%) at week 24. Difference (95% CI) between groups in change in affected BSA from week 12 to week 24 was 4.9% (−23.4%, 33.2%). Conclusion: Patients who received etanercept 50 mg QW at week 12 plus as‐needed topical therapy and those who stayed on etanercept 50 mg BIW maintained clinical response through week 24 with no notable differences in PASI responses.